RDNA-14. RADIATION-INDUCED miR-4516 CONTRIBUTES TO RADIO-RESISTANCE AND PROMOTES AGGRESSIVE PHENOTYPE IN GLIOBLASTOMA. (11th November 2019) - Sebastian, Ebin; Cui, Tiantian; Hlavin Bell, Erica; McElroy, Joseph; Johnson, Benjamin; Manchanda Gulati, Pooja; Geurts, Marjolein; Paixao Becker, Aline; Fleming, Jessica; Jaharul Haque, S; Robe, Pierre; Chakravarti, Arnab
Abstract: BACKGROUND: Glioblastoma is the most aggressive brain tumor with poor prognosis despite the best available treatment. MicroRNAs (miRNAs) are emerging as promising, novel prognostic biomarkers and therapeutic targets in glioblastoma. In a previous study, we demonstrated that miR-4516 predicts poor prognosis and functions as an oncogene in glioblastoma. Aim of the current study is to examine the role miR-4516 in radiation resistance and identify downstream targets contributing to this phenotype METHODS: Radiosensitization was evaluated by cell viability and clonogenic assays. Cell apoptosis was evaluated using flow cytometry and immunoblotting. Potential targets of miR-4516 were identified using bioinformatic analysis (Targetscan and miRDB) and confirmed by luciferase reporter assays. Results were validated using immunoblotting. miR-4516 expression in glioblastoma cell lines after radiation treatment was quantified by qRT-PCR. RESULTS: Expression of miR-4516 was increased up to 15 fold following radiation treatment, peaking at around 15min-60 min in primary and established glioblastoma cell lines including GBM 08-387, GBM 30 and U87-MG. Furthermore, inhibition of miR-4516 sensitized GBM 08-387, GBM30 and U87-MG cells to radiation in comparison to control groups as determined by cell viability and clonogenic assays. Further, miR-4516 inhibition induced apoptosis in these cell lines following radiation treatment. While conducting mechanistic studies, we found that the tumor-promoting function of miR-4516 was, in part, mediated by inhibition of p21 and PTPN14, two direct targets of miR-4516 CONCLUSION: Our data suggest that radiation induces the expression of miR-4516 in glioblastoma cell lines. This miRNA plays a critical role in radio-resistance and promotes aggressive phenotypes in glioblastoma and therefore, functional analyses of its target pathways may uncover novel therapeutically vulnerable target(s) in glioblastoma. FUNDING: R01CA108633, R01CA169368, RC2CA148190, U10CA180850-01(NCI), Brain Tumor Funders Collaborative Grant, and OSU-CCC (all to AC). The Ton and Patricia Bohnenn Fund for Neuro_Oncology Research (to PR).